The Ripple Effects of Flooding On Women in Isoko-Nation, Delta State, Nigeria - Eniwotu, Arausi Roseline; Otite, Atare (The Indonesian Journal of Social Studies, 2023)
This paper examines the ripple effects of flooding on the roles and economic activities of women in Isoko- Nation, flood-prone areas that exhibit low-lying plain that resides on the coaster region of Delta State. The region attracts high population due to flooding fluvial deposits on the flood plains that serve as fertilizer to boost agricultural activities of the people. Consequent upon this, the socioeconomic development of the region is facing reversing years of progress, socially and economically in response to the rippling effects thus crippling effective and sustainable role of the women. The situation is worsened by lack of infrastructural facilities to encourage alternative income earning activities. And the dearth of the women socio-economic status means the dearth of socio-economic development of the region therefore the need to severe the women from the rippling flood effects is vital to the sustainable development of the region. Therefore the paper discussed the implications of the downgrading and reversed economic activities of the women on the sustainable development in the region and noted that though the annual flooding occurrence in the region cannot be completely eliminated however the associated disasters can be mitigated and the rippling effects reduced. The paper recommends that a proper understanding of the season and dynamic climatic trends of the region will create conscious knowledge on the mitigation strategies to reduce the unprecedented effect of incessant flooding and ginger the effort of the government to fulfill its commitment of improving the quality of lives and standard of living in Isoko-nation. The study substantiate that provision of infrastructure would energize the women whose socio-economic status is on the decline to embrace alternative source of income that would revive their hope and faith in the economy of the region.